The Effect of Soy Milk on Reducing Primary Dysmenorrhea Pain in Adolescent Girls at SMK Puspa Bangsa Banyuwangi: THE EFFECT OF SOY MILK ON REDUCING PRIMARY DYSMENORRHEA PAIN IN ADOLESCENT GIRLS AT SMK PUSPA BANGSA BANYUWANGI - Wahyudi, Gufron; Nursanti, Devy Putri (LPPM STIKes Bahrul Ulum Jombang, 2025)
Primary dysmenorrhea is one of the most common complaints among adolescent girls and significantly affects their quality of life. Non-pharmacological management such as calcium-rich nutritional intake is considered an alternative solution. Soybeans are a good source of calcium and isoflavones, which are believed to help reduce menstrual pain. Objective: To determine the effect of soy milk consumption on the reduction of primary dysmenorrhea pain in adolescent girls. This study used a quasi-experimental design with a pretest-posttest with control group approach. The sample consisted of 20 respondents, divided into two groups of 10. The intervention group was given soy milk, while the control group received health education. Data were analyzed using Paired Sample T-Test and Independent T-Test. Results: The analysis showed a significant difference in the reduction of dysmenorrhea pain scale before and after the intervention, with a p-value = 0.000 (p < 0.05). The group that received soy milk experienced a greater reduction in pain compared to the control group. Soy milk has a significant effect on reducing primary dysmenorrhea pain in adolescent girls. This effect is likely due to the calcium and isoflavone content in soy, which plays a role in uterine muscle contraction.